Rethinking Receivership - Armour, J; Frisby, S (Oxford University Press, 2001)
It is a popular perception that administrative receivers and their appointors hold «too much» power in relation to troubled companies. Many who hold this view have called for the reform of insolvency law in order to redress the balance of power. This issue is timely, because insolvency law is currently under review. This article argues that although the law's formal structure is imbalanced, it can nevertheless generate savings for parties, by allowing a concentrated creditor who has invested in information-gathering about the debtor to conduct a private insolvency procedure. It is suggested that this procedure is likely to be more efficient than one conducted by a state official, and that it is likely to reduce the costs of debt finance, a matter of particular importance for small and medium-sized businesses. Empirical data are presented from 26 interviews with practitioners, which shed further light on the operation of receivership. Finally, the current law is compared with possible alternatives. It is argued that the case for wide-ranging reform is not made out.